Utilization of Bioindicators in Environmental Biomonitoring: A Comprehensive Review - Misya, Meilyn; Prasetya, Johan Danu (Jurnal Lingkungan Kebumian Indonesia, 2023)
Environmental biomonitoring is the latest branch of science in modern environmental science. The concept allows the monitoring of environmental quality by involving the use of organisms as a measure of contamination levels. This comprehensive review showcases the latest advances in the field of environmental science with emphasis on innovative methodologies, technological breakthroughs and implications for environmental understanding and management. The review discusses the types of bioindicators that have been used and their respective benefits. Rapid monitoring of environmental quality through biomonitoring helps equip policy makers and stakeholders with critical data and facilitates evidence-based decision making. Further research in this field is needed as it can be a feasible alternative to rapid, low-cost and practical environmental monitoring.